Dynamical model of the dielectric screening of conjugated polymers - Barford, W; Bursill, R; Yaron, D (2004)
A dynamical model of the dielectric screening of conjugated polymers is introduced and solved using the density matrix renormalization group method. The model consists of a line of quantized dipoles interacting with a polymer chain. The polymer is modelled by the Pariser-Parr-Pople (P-P-P) model. It is found that: (1) Compared to isolated, unscreened single chains, the screened 1Bu- exciton binding energy is typically reduced by ca. 1 eV to just over 1 eV; (2) Covalent (magnon and bi-magnon) states are very weakly screened compared to ionic (exciton) states; (3) Screening of the 1Bu- exciton is closer to the dispersion than solvation limit.